2012
DOI: 10.12816/0002236
|View full text |Cite
|
Sign up to set email alerts
|

Mediating Character of Readiness to Change between Training and Development and Employees Performance

Abstract: The purpose of this paper is to explore the liaison of training and development with employee's performance at workplace, also aimed to identify the role of training & development in modifying employees' behavior for Readiness to change. A self-administered questionnaire was designed and filled from call center employees of all five cellular companies in Pakistan. This study will help management to find out the employees attitude regarding training & development that enhance employees performance positively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
1
4
0
2
Order By: Relevance
“…The results of the Sobel test indicate that there is a mediating effect of readiness to change between training on teacher performance. This is supported by the results of research conducted by Asim et al (2012) were the results in this study state that readiness to change has a mediating effect between training on performance. The results of this test which has been carried out with path analysis and t-test where the development variable has a significant effect on the teacher performance variable.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…The results of the Sobel test indicate that there is a mediating effect of readiness to change between training on teacher performance. This is supported by the results of research conducted by Asim et al (2012) were the results in this study state that readiness to change has a mediating effect between training on performance. The results of this test which has been carried out with path analysis and t-test where the development variable has a significant effect on the teacher performance variable.…”
Section: Resultssupporting
confidence: 82%
“…Based on the results of research conducted by Asim, et al (2012) showed that training and development have a significant and positive relationship to employee performance through readiness to change so that the hypothesis can be found: H1: Training has a positive and significant effect on teacher performance H2: Training positive and significant impact on teacher performance mediated by a readiness to change H3: Development has a positive and significant effect on teacher performance H4: Development has a positive and significant effect on teacher performance mediated by a readiness to change The research method used is the survey research method. Data was collected by distributing questionnaires.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Saeed et al (2014) menyatakan bahwa prestasi kerja adalah keterampilan yang dimiliki oleh seorang karyawan untuk melakukan berbagai pekerjaan yang berkaitan dengan kebutuhan pekerjaan. Menurut Borman dan motowidlo dalam Asim et al (2012) menyatakan bahwa prestasi kerja adalah sebuah hasil kerja yang dilakukan karyawan dari waktu ke waktu. Prestasi kerja adalah suatu hasil kerja yang dicapai seseorang dalam melaksanakan tugas-tugas yang dibebankan kepadanya yang didasarkan atas kecakapan, pengalaman, dan kesungguhan, serta waktu (Hasibuan & Malayu, 2013).…”
Section: Pendahuluanunclassified
“…Prestasi kerja adalah suatu hasil kerja yang dicapai seseorang dalam melaksanakan tugas-tugas yang dibebankan kepadanya yang didasarkan atas kecakapan, pengalaman, dan kesungguhan, serta waktu (Hasibuan & Malayu, 2013), Menurut Borman dan motowidlo dalam Asim et al (2012) prestasi kerja adalah sebuah hasil kerja yang dilakukan karyawan dari waktu ke waktu. Sutrisno & Edy (2009) menyatakan prestasi kerja adalah hasil upaya seseorang yang ditentukan oleh kemampuan karakteristik pribadinya serta terhadap peran pekerjaanya.…”
Section: Pendahuluanunclassified
“…Telecom sector is most rapidly growing sector of Pakistan and this sector has seen many changes during past few years including changes for requirement of technology, coverage of network and escalating competition, so these changes resulted in requirement of well trained employees (Sultana et al, 2012). There is an intensifying competition among companies in telecom sector of Pakistan in the form of innovation, new technology and pricing etc., so mobile operator companies of Pakistan needs to prepare their employees for upcoming challenges and they should be ready to accept the changes and enhance their performance (Asim et al, 2012). Mobile and telecom technology are advancing rapidly, GSM and internet enabled tablets and mobile phone devices will be used (Imtiaz et al, 2015).…”
Section: Introductionmentioning
confidence: 99%